The association of niobian rutile, columbite-group minerals and uranium-rich pyrochlore in the Rancul granitic pegmatite, San Luis, Argentina - Galliski, Miguel Angel (2024)
We describe the mineralogy of the association of accessory niobian rutile, columbite-group minerals and an uranium-rich pyrochlore- like phase that occur in the Rancul property (32º38´50” S, 65º40´46” W), an NYF intragranitic pegmatite of the Potrerillos group, San Luis, Argentina. Other accessory and secondary minerals include biotite, muscovite, beryl, schorl, apatite, ilmenite, pyrite, bismuthinite, clinobisvanite, hematite, and goethite. Niobian rutile occurs as rare cm-sized prismatic crystals in the core-margin assemblage usually enclosed in quartz or albite. It has Ti# [Ti/(Ti+Nb+Ta)] variable between 0.81 and 0.92 and contents of TiO2 between 63.46 and 80.21 wt.%, Nb2O5 ≤ 21.66 wt.%, most of the iron as Fe2O3, low UO2 and Sc2O3. The contents (wt.%) of Ta2O5 are variable, reaching up to 7.86, of WO3 ≤ 1.46, of SnO2 ≤ 1.12, of Sc2O3 ≤ 0.37 and of ZrO2 ≤ 0.15. The structure is that of monorutile (space group P42/mnm) and the cell parameters are a = 4.622 (2) Å; c = 2.983 (2) Å; V = 63.73 (5) Å3. The rutile has inclusions of a columbite-group mineral, likely disordered columbite, and a U-rich pyrochlore-group mineral with up to 53.66 wt.% of UO2 accompanied by niobian rutile with higher Ti# and lower content of trace elements. They are not exsolution products and were produced along subparallel cracks possibly by Ca,Mn,U-rich aqueous fluids that reworked the primary niobian rutile leaching the trace elements and crystallizing the new mineral phases.